Squamous cell carcinoma of the lip: depth of invasion, local recurrence and regional metastases. Experience of a rural multidisciplinary head and neck unit. (25th August 2015) - Pastuszek, A; Hanson, M; Grigg, R
Abstract: Background: The internationally recognised American Joint Committee on Cancer (tumour–node–metastasis) staging system utilises tumour size to determine stage. Other factors (i.e. tumour depth) may provide additional prognostic information. Method: A thorough retrospective analysis was performed of 68 patients with primary lip squamous cell carcinoma operated on or discussed by the Darling Downs Health Service between 2005 and 2013. Results: Twelve patients developed lymphatic spread. There was a statistically significant increased risk of nodal metastasis in: patients with tumours of increased thickness (U = 103.50; degrees of freedom = 68; p  < 0.001), those with a larger overall tumour size (U = 163.50; degrees of freedom = 68; p  = 0.005) and patients living further from the treatment centre (U = 199.00; degrees of freedom = 68; p  = 0.018). Conclusion: It may be reasonable that other factors are considered for staging of lip squamous cell carcinomas, in combination with tumour–node–metastasis staging. Depth of invasion may have utility in prognosis and treatment; however, larger prospective analysis needs to be performed. Patients living in a more rural setting presented with more advanced disease, suggesting an ongoing rural–metropolitan gap in healthcare.